Pendampingan Pekerjaan Perencanaan Renovasi Mesjid Nur Ikhlas Kelurahan Sukagalioh Kecamatan Sukajadi - Choly Nuradil (Institut Teknologi dan Bisnis Semarang, 2025)
Assistance activities carried out in planning the renovation of the Nur Ikhlas Mosque in Sukagalih Village, Sukajadi District, with the aim of helping the local community plan the renovation of the mosque so that it can meet the functional and aesthetic needs expected by the community. The mentoring process involves analyzing the current condition of the building, identifying community needs, and developing two alternative renovation plans. The community is actively involved in every planning stage, so they have a sense of ownership of the final result. It is hoped that this activity can improve the quality of worship facilities and strengthen social ties between residents.